Sosialisasi Pencegahan Stunting melalui Konseling Kesehatan dan Gizi Anak di TK Islam Bakti 1 Ngesrep Boyolali Jawa Tengah - Nurul Ilmi Azizah, Annafi; Aura Septia Maharani, Rizka; Nur Farida, Latifa; Insani Madani, Risma; Alya Putri, Titania; Nur Ash Sholihah, Zulfa; Hansa Luqmanah Hakim, Auliaul; Salsa Rahmawati, Mareta; Eka Bunga, Viona (Mulya Literasi Publishing, 2024)
Stunting caused by chronic malnutrition, can affect physical growth, cognitive development, and the quality of life of children in the future. The activities conducted on December 14 and 16, 2024, include education about healthy and unhealthy foods, fruit satay-making practice, and interactive discussions involving children and their caregivers. The method used is interactive socialization through an educational approach, such as discussions, games, and hands-on practice. This approach is designed to provide children with both theoretical understanding and practical experience regarding the importance of balanced nutrition. The results of the activities show an increase in children's understanding of the concept of nutritious food, the ability to distinguish between healthy and unhealthy food, and enthusiasm for adopting healthy eating habits. Early nutrition education with enjoyable and practical methods is effective in increasing children's awareness of the importance of balanced nutrition to support optimal growth and development while also preventing the risk of stunting.